Association Between Vertical Bone Defects and Interdental Papilla Loss in Periodontitis: A Cross-Sectional Analysis - Hristina Maynalovska; Kamen Kotsilkov (Dentistry Journal, 2025)
Background: The interdental papilla plays a critical role in maintaining both the esthetic and functional integrity of the periodontium. Although the relationship between the papilla presence and the contact point–bone crest distance is well established, the impact of vertical bone defect morphology—common in periodontitis—remains largely unexplored. Aim: To assess the relationship between the loss of interdental papilla height and three site-specific factors—vertical bone defect morphology, probing depth, and papilla base width—in patients with periodontitis. Materials and Methods: Ten periodontitis patients contributing 28 interdental papillae adjacent to vertical bone defects were included. The recorded parameters included probing depth, papilla base width, and loss of papilla height. Intraoperative measurements of defect depth, mesiodistal width, and buccolingual width were also obtained. Patient-level variables, such as age, sex, oral hygiene, and gingival phenotype, were not controlled or included in the analysis, due to the small number of participants and the study’s focus on defect-level characteristics. Spearman’s rank correlation was used due to non-normal data distribution. Results: A moderate positive association was observed between the probing depth and loss of papilla height (ρ = 0.353), approaching but not reaching statistical significance (p = 0.066). Weak, non-significant associations were found with the remaining parameters (p > 0.05). Conclusions: Although no statistically significant associations were found, observed trends may indicate site-specific influences on the loss of papilla height. These preliminary findings highlight the need for further research with larger, well-characterized cohorts to better understand the factors affecting papilla stability in periodontitis.